Logistics and transport modeling in urban goods movement - Gonzalez-Feliu, Jesus (IGI Global, 2019)
"This book examines urban goods transport. It addresses quantitative methods of transport modelling, applied to freight/goods transport in urban areas. It also gives an overview as well as a set of methodological proposals to model urban goods transport flows for planning and management issues"- Resumé vydavatel
Keywords: nákladní doprava; logistika (management); městská doprava; freight traffic; business logistics; urban transportation; electronic books; monographs; monografie; elektronické knihy